2017
DOI: 10.1111/jors.12364
|View full text |Cite
|
Sign up to set email alerts
|

Does EU cohesion policy work? Theory and evidence

Abstract: This paper evaluates the effectiveness of European Cohesion Policy in the regions of 12 EU countries in the period 1991–2008, on the basis of a spatial growth model, which allows for the identification of both direct and indirect effects of EU funds on GDP per worker growth. We find that “Objective 1” funds are characterized by strong spatial externalities and a positive and concave effect on the growth of GDP per worker, which reaches a peak at the ratio funds/GDP of approximately 3 percent and becomes non-si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 67 publications
(167 reference statements)
3
32
0
5
Order By: Relevance
“…Both frameworks allow for testing the effect of the policies interventions at the regional level (Fabrizi, Guastella, Marta, & Timpano, 2016). The studies that test the regional convergence of per capita income or labour productivity in Europe generally confirm the prediction of convergence, finding higher growth rates in the least developed regions (Fiaschi, Lavezzi, & Parenti, 2018; Guastella & Timpano, 2016; Pellegrini, Terribile, Tarola, Muccigrosso, & Busillo, 2013). In some cases, however, researchers find diverging dynamics among European regions (Perugini & Signorelli, 2004; Petrakos & Artelaris, 2009), highlighting that regional economic performance varies according to national characteristics (Cuaresma, Doppelhofer, & Feldkircher, 2014; Crescenzi & Giua, 2020).…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Both frameworks allow for testing the effect of the policies interventions at the regional level (Fabrizi, Guastella, Marta, & Timpano, 2016). The studies that test the regional convergence of per capita income or labour productivity in Europe generally confirm the prediction of convergence, finding higher growth rates in the least developed regions (Fiaschi, Lavezzi, & Parenti, 2018; Guastella & Timpano, 2016; Pellegrini, Terribile, Tarola, Muccigrosso, & Busillo, 2013). In some cases, however, researchers find diverging dynamics among European regions (Perugini & Signorelli, 2004; Petrakos & Artelaris, 2009), highlighting that regional economic performance varies according to national characteristics (Cuaresma, Doppelhofer, & Feldkircher, 2014; Crescenzi & Giua, 2020).…”
Section: Introductionmentioning
confidence: 74%
“…The latter effect especially appears when a region entitled to the funds stops receiving them (Barone, David, & de Blasio, 2016; Becker, Egger, & von Ehrlich, 2018). On the contrary, there is agreement on the fact that the impact of CP on regional convergence depends on several regional characteristics, such as the human capital and infrastructure endowments (Becker, Egger, & von Ehrlich, 2013; Esposti & Bussoletti, 2008), the sector in which the funds are spent (Rodríguez‐Pose & Fratesi, 2004), the funds' concentration (Fiaschi et al, 2018; Mohl & Hagen, 2010) or the quality of the regional institutions (Rodríguez‐Pose, 2013; Rodríguez‐Pose & Garcilazo, 2015; Rodríguez‐Pose & Ketterer, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Despite growing interest on the part of academics, no consensus has been reached on whether cohesion policy spending contributes to the economic and social cohesion of European regions (Bachtler et al 2016). While some studies have shown that it increased territorial cohesion (Fiaschi et al 2018;Rosik et al 2017;Pontarollo 2017), others have stressed that, in specific contexts, cohesion policy might have no, or even negative effects on territorial cohesion (Bachtrögler et al 2019;Kroll 2017;Medve-Bálint 2017). Only recently have studies added the dimension of European identity to cohesion policy evaluations (Aiello et al 2018;Borz et al 2018;Pegan et al 2018), which is surprising considering that strengthening European solidarity is one of the main rationales behind the idea of a Europe-wide investment policy (European Commission 2019).…”
Section: Evaluating Eu Cohesion Policymentioning
confidence: 99%
“…The social oriented market economy system which is predominant in the European Union, and despite decreasing the profit margins for businesses on overall, it is favourable for SMEs (Medve-Bálint, 2018). Yet, its success is spread unevenly due to the heterogeneity in terms of institutional efficiency (Fiaschi et al, 2018). Jorgenson et al (2014) pointed that present economic development should be sustainable to permit the future generations to satisfy their needs.…”
Section: Literature Reviewmentioning
confidence: 99%